PERAN PENGELOLA RUMAH BACA PESISIR (RBP) DALAM MENINGKATKAN MINAT BACA ANAK DI KECAMATAN SANROBONE KABUPATEN TAKALAR - Muh Fadli; Latang Latang; Muhammad Asri (JAPPA: Jurnal Andragogi Pedagogi dan Pemberdayaan Masyarakat, 2024)
The purpose of this study is to describe the Role of Coastal Reading House Management in Increasing Children's Reading Interest in Sanrobone District, Takalar Regency. This research approach is a qualitative approach with a case study type of research. The subjects of this study were the head of the reading house, the manager of the reading house, and visitors to the Coastal Reading House. Data collection techniques are carried out by interviews, observation and documentation. Data analysis uses data reduction, data presentation and conclusions. The triangulation used is the triangulation of sources and methods. The results showed that coastal reading house managers play an important role in increasing children's interest in reading, with their roles as informators, facilitators, motivators and innovators. Researchers can conclude that the role of the Reading House Manager has been realized, including the role as an informator has been realized by becoming the main source of information related to coastal reading houses. . The role as a facilitator has been realized by providing and providing services related to facilities for activities in coastal reading houses. The role as a motivator has been realized, this is characterized by providing encouragement to develop children's interest in reading. The role as an innovator has been realized by carrying out an innovation that aims to foster the attraction of children to want to visit and do reading activities at reading houses.Keywords: Manager role, Reading interest, Reading House